Global incidence and mortality of breast cancer: a trend analysis - Junjie Huang; Paul Chan; Veeleah Lok; Xiao Chen; Hanyue Ding; Yinzi Jin; Jinqiu Yuan; Xiang Qian Lao; Zhi‐Jie Zheng; Martin C. S. Wong (2021)
This study aimed to evaluate the global incidence and mortality trends of breast cancer among females by region and age in the past decade. We retrieved country-specific incidence and mortality data from the Global Cancer Observatory up to 2018 and Cancer Incidence in Five Continents volumes I-XI, the Nordic Cancer Registries, the Surveillance, Epidemiology, and End Results, and WHO mortality database up to 2016. The temporal patterns were using Average Annual Percent Change (AAPC) with the 95% confidence interval (CI) by joinpoint regression analysis. Most countries showed an increasing trend in incidence. For the older population aged ≥ 50 years, Japan (5.63, 4.90-6.36), Slovakia (3.63, 3.03-4.22), China (2.86, 2.00-3.72) reported the most prominent increase. For young females (<50 years), Japan (AAPC=3.81, 95% CI=2.71-4.93), Germany (AAPC=2.60, 95% CI=1.41-3.81) and Slovakia (1.91, 1.13-2.69) reported the most drastic rise. Similarly, 12 countries showed an incidence increase among women aged <40 years. As for mortality, the Philippines (4.36, 3.65-5.07), Thailand (4.35, 3.12-5.59), Colombia (0.75, 0.08-1.42), and Brazil (0.44, 0.19-0.68) reported a significant increase. The disease burden of breast cancer showed an increasing trend in a large number of populations. More preventive efforts are recommended for these countries. Further research should explore the underlying reasons for these epidemiological trends.